2005
DOI: 10.1089/hum.2005.16.1276
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Lipoprotein Lipase Deficiency: Working Toward Clinical Application

Abstract: Lipoprotein lipase (LPL) deficiency causes hypertriglyceridemia and recurrent, potentially life-threatening pancreatitis. There currently is no adequate treatment for this disease. Previously, we showed that intramuscular administration of an adeno-associated virus serotype 1 (AAV1) vector encoding the human LPL(S447X) variant cDNA (AAV1-LPL(S447X)) normalized the dyslipidemia of LPL-/- mice for more than 1 year. In preparation for a clinical trial, we evaluated the safety and biodistribution of AAV1-LPL(S447X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…This not only allows for a large portion of the AAV genome to be replaced with a therapeutic transgene but also the packaging of an AAV2-derived genome by capsid (Cap) proteins from other serotypes, resulting in AAV2 with altered tropism and immunogenicity. The recombinant vector used for this study, AAV1-LPL S447X , was produced in this way, using Cap proteins from AAV serotype 1 and ITRs from AAV2 (Rip et al, 2005).…”
Section: The Vectormentioning
confidence: 99%
See 2 more Smart Citations
“…This not only allows for a large portion of the AAV genome to be replaced with a therapeutic transgene but also the packaging of an AAV2-derived genome by capsid (Cap) proteins from other serotypes, resulting in AAV2 with altered tropism and immunogenicity. The recombinant vector used for this study, AAV1-LPL S447X , was produced in this way, using Cap proteins from AAV serotype 1 and ITRs from AAV2 (Rip et al, 2005).…”
Section: The Vectormentioning
confidence: 99%
“…In addition to the lower seroprevalence, AAV1 vectors transduce skeletal muscle with substantially higher efficiency than is observed with AAV2. Given that skeletal muscle is a site for physiological expression of LPL, the efficiency of transduction in this tissue made AAV1 an attractive vector for delivery of the LPL transgene (Rip et al, 2005).…”
Section: The Vectormentioning
confidence: 99%
See 1 more Smart Citation
“…These include Canavan disease, 94 a-1-antitrypsin deficiency, 95 late infantile neuronal ceroid lipofuscinosis 96 and lipoprotein lipase deficiency. 97 All are phase I or I/II. Two of these conditions, Canavan disease and late infantile neuronal ceroid lipofuscinosis, involve targeting of the central nervous system and necessitate the enrolment of children.…”
Section: Clinical Trials For Metabolic Diseasementioning
confidence: 99%
“…20 It was found that muscle is well-suited to dose-dependent LPL expression and that skeletal muscle is tolerant to high viral loads. 18 Additionally, acute inflammatory elements are only transiently elevated post-injection in mice.…”
mentioning
confidence: 99%